2020
DOI: 10.1002/aelm.201901402
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Poly(Vinyl Alcohol)–Graphene Oxide Hybrid Nanocomposite Based Cognitive Memristor with Pavlovian‐Conditioned Reflex Activities

Abstract: Recently, neuromorphic devices have attracted great attention in the field of artificial intelligence technology at the hardware level. In particular regarding the developments of flexible electronics, there is an increasing interest in brain‐inspired multi‐functional perception learning system. In the present work, flexible cognitive memristors based on poly(vinyl alcohol)–graphene oxide (PVA‐GO) hybrid nanocomposite are proposed. These devices exhibit excellent electrical performance at ultralow voltage belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…2D materials have been regarded as a class of promising candidates for next-generation electronic devices, neuromorphic electronics and artificial sensory systems, due to their appealing physical, chemical and electronic features [26,[64][65][66][67][68][69]. 2D materials possess a lot of unique characteristics such as ultrathin thickness, large specific surface area, excellent mechanical flexibility, and high transparency, which endow them with potential of implementing high-performance flexible and wearable electronics.…”
Section: D Materials-based Flexible Memristorsmentioning
confidence: 99%
See 2 more Smart Citations
“…2D materials have been regarded as a class of promising candidates for next-generation electronic devices, neuromorphic electronics and artificial sensory systems, due to their appealing physical, chemical and electronic features [26,[64][65][66][67][68][69]. 2D materials possess a lot of unique characteristics such as ultrathin thickness, large specific surface area, excellent mechanical flexibility, and high transparency, which endow them with potential of implementing high-performance flexible and wearable electronics.…”
Section: D Materials-based Flexible Memristorsmentioning
confidence: 99%
“…As the early member of 2D materials family, GO and its derivatives (e.g., polymer-functionalized GO, TiO 2 -assisted GO, and GO/biomaterial composites) have been intensively investigated for fabricating flexible devices, which succeed in realizing the reliable memristive switching behaviors [65,[73][74][75]. For instance, Jeong et al [45] reported the fabrication of a flexible memristor by utilizing GO as the active layer (Fig.…”
Section: D Materials-based Flexible Memristorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar way, monophasic PSC induced by subthreshold stimuli in the form of either EPSC or IPSC, is widely emulated by various synaptic devices. [41][42][43][44][45][46][47][48][49][50][51] However, biphasic PSC triggered by suprathreshold stimuli is hardly implemented by artificial synaptic electronics. Nevertheless, as depicted in Figure 2a, the fabricated devices with NaAc doped PVA electrolyte exhibit biphasic PSC under a single spike with 1 mV amplitude and 100 ms width.…”
Section: Biphasic Postsynaptic Currentmentioning
confidence: 99%
“…[40] Given those superior merits, PVA has been exploited in electrochemical synaptic transistors as protonconducting electrolytes, [41][42][43][44][45] or served as an active layer in the synaptic resistive switching device. [46] Despite successful emulation of synaptic behaviors, similar problems perplex these artificial synapses, which stimulate at high spike voltage (≈1.5-9 V) and consume a large amount of power (≈7.29 pJ-3.75 uJ). Although applying ultrafast stimulation (e.g., nanosecond) helps to reduce the energy consumption of artificial synapses (using other materials and structures), [47][48][49][50][51] the stimulating voltage still remains high compared to mV-level nerve pulses.…”
Section: Introductionmentioning
confidence: 99%